2020
DOI: 10.1177/1535676020947284
|View full text |Cite
|
Sign up to set email alerts
|

A Rapidly Deployable Test Suite for Respiratory Protective Devices in the COVID-19 Pandemic

Abstract: Introduction: The current COVID-19 pandemic has caused large shortages in personal protective equipment, leading to hospitals buying their supplies from alternative suppliers or even reusing single-use items. Equipment from these alternative sources first needs to be tested to ensure that they properly protect the clinicians that depend on them. This work demonstrates a test suite for protective face masks that can be realized rapidly and cost effectively, using mainly off-the-shelf as well as 3D printing comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…PFE of masks was measured using an approach based on the requirements of EN 149:2001+A1:2009 (EN 149+A1). 23 Firstly, we need to adjust the filtration efficiency detection system to the detection state, and set the related test parameters. Then connect the filter element to the detection device in an airtight manner with a suitable clamp.…”
Section: Methodsmentioning
confidence: 99%
“…PFE of masks was measured using an approach based on the requirements of EN 149:2001+A1:2009 (EN 149+A1). 23 Firstly, we need to adjust the filtration efficiency detection system to the detection state, and set the related test parameters. Then connect the filter element to the detection device in an airtight manner with a suitable clamp.…”
Section: Methodsmentioning
confidence: 99%
“…A project at the University of Delft used a validated method that clearly demonstrated that carbon dioxide re-breathing under standardised laboratory conditions (test suite) after 1 minute is at least 0.9% CO 2 for N95/ FFP2 masks [20]. Those elevated carbon dioxide levels of inhaled air, particularly under N95 masks, have also been found in physiologic relevant short-time modeling studies.…”
Section: Effects Of Masks On Carbon Dioxide Re-breathingmentioning
confidence: 98%
“…This is because carbon dioxide is heavier than other air components (approximately 44 g/mol in CO 2 compared to 32 g/mol in O 2 and 28 g/mol in N 2 ) and could accumulate there over time to a lesser extent than in the lower parts of the dead space of the mask [21]. In contrast, Butz provided a positioning of the sensor close to the mouth attached to the cheek [18], like Blad [20] and Sinkule [23], who placed it close to the breathing orifice (mouth opening), while Rhee and Roberge chose the nasolabial fold [25,27].…”
Section: Effects Of Masks On Carbon Dioxide Re-breathingmentioning
confidence: 99%
See 2 more Smart Citations